Daily shifts in regulatory focus: The influence of work events and implications for employee well‐being. (28th March 2016) - Koopmann, Jaclyn; Lanaj, Klodiana; Bono, Joyce; Campana, Kristie
Summary: Although theory suggests that regulatory focus fluctuates within person and such fluctuations impact employee well‐being, there is little empirical investigation of such propositions. These are important research questions to address because work events may elicit within‐person fluctuations in regulatory focus, which can then affect well‐being. The primary purpose of this study is to examine specific predictors of daily regulatory focus at work and the foci's impact on employee well‐being at work and home as indicated by mood and psychosomatic complaints, respectively. We present and test an overarching theoretical framework that integrates conservation of resources theory, the cognitive‐affective processing system framework, and regulatory focus theory to delineate why and when work events affect regulatory focus and how the foci affect well‐being. Consistent with our expectations, we found that positive work events positively predicted daily promotion focus, but this effect was weaker when employees had high‐quality relationships with leaders. Furthermore, daily regulatory focus was associated with employee well‐being (mood and psychosomatic complaints) such that (i) promotion focus improved well‐being; (ii) prevention focus reduced well‐being; and (iii) the effects of promotion focus on well‐being were strongest when prevention focus was low. We discuss theoretical and practical implications and offer directions for future research. Copyright © 2016 John Wiley & Sons, Ltd.